Lattices Generated by Information Systems and their Internal Structure - Winkowski, Józef (Journal of Advances in Management Sciences & Information Systems, 2018)
The paper exploits the fact that every information system generates a family of equivalence relations in the set of considered objects, and the corresponding family of partitions of this set, and that this family is a lattice with certain properties. It describes the internal structure of any lattice with sucThe paper exploits the fact that every information system generates a family of equivalence relations in the set of considered objects, and the corresponding family of partitions of this set, and that this family is a lattice with certain properties. It describes the internal structure of any lattice with such properties and shows that such a lattice is generated by an information system